NEW NOTIONS ADAPTED TO THE ARABIC LANGUAGE IN THE CONTEXT OF THE COVID-19 PANDEMIC (Romano-arabica, 2025)
The adaptation of new or foreign concepts to the Arabic language is a difficult and ongoing struggle, due to its morphological particularities (Elmgrab, 2016: 75-85). This article endeavours to present a series of notions brought to the attention of the general public in the context of the COVID-19 pandemic and their adaptation to the Arabic language. The study was conducted based on online materials and articles, as well as on Internet queries for the period 2020-2024. The analysis focused mainly on articles identified on the Al-Jazeera platform, which served as a base for specific examples and statistics. The aim of the article is to follow the degree of terminological consistency with regards to the adapted notions, as well as to identify the processes based on which the adapted Arabic syntagms were formed.